Performers and players - Franck, Irene M. 4 0 16; Brownstone, David M.; 5 (New York : Facts on File, 1988)
Traces the development of entertainers and athletes and includes historical profiles.
Includes index.
Bibliography: p. 183-188.
School Library Journal
8.8;Young Adult;Young Adult
Keywords: 2 -- 0; 6; History;Vocational guidance;History;Vocational guidance;History.;Vocational guidance.;History.;Vocational guidance. -- Performing arts;Entertainers;Sports;Athletes;Performing arts;Entertainers;Sports;Athletes -- Juvenile literature.;Juvenile literature.;Juvenile literature.;Juvenile literature; 20; 2